A Soluble Fibrin Standard: Comparable Dose-response with Immunologic and Functional Assays - McCarron, Bonnie I.; Marder, Victor J.; Kanouse, Joel J.; Francis, Charles W. (Thrombosis and Haemostasis, 1999)
A soluble fibrin (SF) preparation has been developed as a potential standard by the Scientific and Standardization Committee for use in assays evaluating in vitro preparations and patient plasma samples. The SF standard was prepared by reaction of factor XIII-free fibrinogen with thrombin, followed by neutralization with hirudin and solubilization of the fibrin in acetic acid. As characterized by SDS-PAGE, the polypeptide chain structure shows the anticipated loss of fibrinopep-tides and lack of sγ or α chain crosslinking. The standard was added to pooled normal plasma at concentrations from 12.5 μg/ml to 340 μg/ml and tested with four commercially available assays based on immunologic reactions using ELISA or latex agglutination or on t-PA cofactor activity for plasminogen to plasmin conversion. Absolute “soluble fibrin” concentrations were calculated using the manufacturers’ calibrators and showed distinct dose-response relationships for each assay. Expression of the results following log-transformation produced a series of parallel lines, indicating that this SF preparation can serve as a standard, effectively normalizing the disparate proprietary internal calibrators currently used for each assay.